Young patient with hypertension and risk factors. Intervention: which, when and for who? - Bryl, Wiesław (Przewodnik Lekarza/Guide for GPs, 2007)
In the literature there have been presented issues related with hypertension combined with other heart vessel risk factors in children and adolescents. Rules of prevention and treatment activities are put forward focused on the young hypertensive as an individual as well as on the family environment. Current strategy and guidelines of the American Heart Association are taken into consideration, referring to basic prophylaxis of coronary diseases in children. Rules of pharmacological treatment are also presented as well as recommended groups of drugs in children and adolescents with hypertension.